Evaluation of the effectiveness of psychological capital intervention of Luthans on job burnout in the experts working in Iran Khodro Diesel Company - A Alipour; M Saffari nia; GR Sarami Forushani; AM Agha Alikhani; N Akhundi (طب کار)
Background: Psychological capital intervention of Luthans (PCI) is a training program whose effectiveness on decreasing some work-related problems has been confirmed. Therefore, it could be possible to reduce job burnout which is considered of work-related side effects, with devastating effects on individual and organization. The aim of present study was to evaluate the effectiveness of Luthans intervention program on job burnout. Methods: The study used a semi-experimental design with pretest and posttest. Statistical population was 650 experts working in Iran Khodro Diesel company. Among them 60 people were selected by random sampling method and divided into two groups of 30 people. Maslach job burnout questionnaire was used as assessment tool. After the implementation of the questionnaire, Luthans intervention program was applied to experimental group after each participant was tested again using questionnaire. Data was analyzed by SPSS software and independent T-test. Results: According to the results, burnout pretest scores show a small difference in both groups (2.87; 2.9). But considering job burnout (2.12) and subscales of emotional exhaustion (1.34) and depersonalization (0.72) the average score has decreased significantly in experimental group post test (p<0.01). There was no significant difference in personal accomplishment (p=0.466), but as questionnaire indicates, the scores of experimental group has changed from moderate to high levels of accomplishment. Conclusion: Given the findings, it can be concluded that Luthans intervention program is effective in reducing job burnout, especially subscales of emotional exhaustion and depersonalization. Therefore, it could be an appropriate strategy to reduce job burnout.